Spousal Individual Retirement Accounts - Lisa Leslie (EDIS)
A spouse who stays at home to take care of children or other dependents is likely to have reduced Social Security benefits and will not have access to a workplace retirement plan. So a spousal Individual Retirement Account (IRA) can be an important step to enabling retirement security. An IRA is a tax-advantaged way to accumulate money for retirement. In order to contribute to an IRA you must have taxable compensation. But if your spouse has taxable compensation and you file a joint return, then you can fund an IRA. This 2-page fact sheet was written by Lisa Leslie, and published by the UF Department of Family, Youth and Community Sciences, November 2014.